2012
DOI: 10.1111/j.1744-9987.2012.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Pulse High‐Volume Hemofiltration on Severe Acute Pancreatitis Complicated With Multiple Organ Dysfunction Syndrome

Abstract: To evaluate the effects of pulse high-volume hemofiltration (PHVHF) on severe acute pancreatitis (SAP) with multiple organ dysfunction syndrome (MODS). Thirty patients were divided into two groups: PHVHF group and continuous venovenous hemofiltration (CVVH) group. They were evaluated in terms of clinical symptoms, acute physiology and chronic health evaluation (APACHE) II score, sequential organ failure assessment (SOFA) score, simplified acute physiology (SAPS) II score and biochemical changes. The levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…We found significant decrease of norepinephrine dose requirement during extended high volume (median 123 mL/kg/h) intermittent haemodiafiltration in patients with septic shock despite negative fluid balance in most patients. This finding is in line with other experimental [ 17 ] and clinical studies with different modalities of high volume haemofiltration [ 7 11 , 18 ]. However, a recent randomized multicentre study, comparing continuous haemofiltration in the dose of 35 mL/kg/h to 70 mL/kg/h [ 12 ], did not show any haemodynamic or survival benefit from higher filtration volumes, yet the study was underpowered, recruiting 140 patients instead of 460 required from power calculation.…”
Section: Discussionsupporting
confidence: 92%
“…We found significant decrease of norepinephrine dose requirement during extended high volume (median 123 mL/kg/h) intermittent haemodiafiltration in patients with septic shock despite negative fluid balance in most patients. This finding is in line with other experimental [ 17 ] and clinical studies with different modalities of high volume haemofiltration [ 7 11 , 18 ]. However, a recent randomized multicentre study, comparing continuous haemofiltration in the dose of 35 mL/kg/h to 70 mL/kg/h [ 12 ], did not show any haemodynamic or survival benefit from higher filtration volumes, yet the study was underpowered, recruiting 140 patients instead of 460 required from power calculation.…”
Section: Discussionsupporting
confidence: 92%
“…In 2004, PHVHF technology was suggested by Brendolan to solve the issue (19). Previous findings showed that for treatment of severe sepsis, PHVHF can improve hemodynamics, decrease inflammatory mediator response, and restore the immune balance (2023). Our results showed that, PHVHF can improve clinical symptoms of patients with severe sepsis, and reduce the APACHE II score.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that 11-30% of SAP patients have ACS, which has a high mortality rate of 30-60%, despite significant improvement in treatment due to the better understanding of the pathophysiology of disease, early aggressive fluid resuscitation, and timely surgical intervention. At present, it is well accepted that SAP patients with SIRS have a high risk of developing ACS [19]. Blood levels of various cytokines are elevated in SAP and among them, the blood level of IL-8 as one of main inflammatory cytokines has been reported to reflect the severity of SAP.…”
Section: Discussionmentioning
confidence: 99%